1999
DOI: 10.1200/jco.1999.17.12.3706
|View full text |Cite
|
Sign up to set email alerts
|

Results of Treatment for Soft Tissue Sarcoma in Childhood and Adolescence: A Final Report of the German Cooperative Soft Tissue Sarcoma Study CWS-86

Abstract: The improved design of the study incorporating risk-adapted radiotherapy allowed treatment to be reduced for selected groups of patients without compromising survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
213
1
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(237 citation statements)
references
References 17 publications
12
213
1
11
Order By: Relevance
“…The prognosis regarding sex, age, pathological subtype and size was in accordance with earlier studies 9, 16, 18. Just as the report by Dantonello et al 16 showed, the primary site category with the best prognosis was the orbit and the worst was the category called other sites.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The prognosis regarding sex, age, pathological subtype and size was in accordance with earlier studies 9, 16, 18. Just as the report by Dantonello et al 16 showed, the primary site category with the best prognosis was the orbit and the worst was the category called other sites.…”
Section: Discussionsupporting
confidence: 87%
“…As expected, there was a slight male predominance and the age distribution was comparable to international data published, as was the distribution of pathological subtype, size and primary site 3, 6, 7, 8, 9, 10. The frequency of metastatic disease for the total cohort was equivalent to that reported in earlier publications 5, 7, 8, 9, 10, but during the last time period, 2000–2010, the metastasis rate at diagnosis was surprisingly high. During the last time period, the rate of metastatic disease was significantly higher than the earlier time periods, with a metastasis rate of 28% compared to 9% in 1984–1989 and 13% in 1990–1999.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations